1987
DOI: 10.1007/bf00586522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of low and high frequency patterns of stimulation on contractile properties, enzyme activities and myosin light chain accumulation in slow and fast denervated muscles of the chicken

Abstract: The effects of denervation and direct stimulation in fast and slow latissimus dorsii muscles were investigated in chicken. In slow ALD muscle, denervation resulted in an incompleteness of the relaxation, a decrease in MDH and CPK activities and an increase in fast myosin light chains (MLC) accumulation. Direct stimulation at either fast or slow rhythm prevented the effects of denervation on relaxation and CPK activity but was ineffective on MDH activity and fast MLC accumulation. Moreover, direct stimulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1988
1988
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…The normal contractile force of muscles from hatchling chicks is lower than the contractile force of adult pigeon extraocular muscles shown in previous studies (571 mN/cm 2 ), 37 possibly due to the difference in stimulus parameters and settings (in vitro versus in situ) and/or the ages of animals between the two studies. 38…”
Section: Contractile Force Of Normal Extraocular Musclementioning
confidence: 99%
“…The normal contractile force of muscles from hatchling chicks is lower than the contractile force of adult pigeon extraocular muscles shown in previous studies (571 mN/cm 2 ), 37 possibly due to the difference in stimulus parameters and settings (in vitro versus in situ) and/or the ages of animals between the two studies. 38…”
Section: Contractile Force Of Normal Extraocular Musclementioning
confidence: 99%
“…The lack of reinnervation of the muscle was verified in a preliminary series of experiments by examination of muscle sections stained using a silver technique (Ungewitter,195 1) to visualize the nerve, and by stimulation of the remaining nerve trunk. In the latter case, no muscular response was elicited (Khaskiye et al, 1987).…”
Section: Chronic Electrical Stimulationmentioning
confidence: 87%
“…Furthermore, direct electrical stimulation of denervated ALD was ineffective in preventing the postdenervation changes in AChE-molecular-form distribution. It has been reported that denervated ALD muscle does not respond as well to electrical stimulation as PLD muscle does, with respect to myosin light chains and to oxidative activity [19]; furthermore, it exhibits less plasticity for transformation after cross-reinnervation experiments [20]. The differential response of ALD muscle to denervation, cross-reinnervation and to direct electrical stimulation emphasizes the existence of intrinsic differences between fast PLD and slow ALD muscles.…”
Section: Discussionmentioning
confidence: 99%
“…Two patterns of stimulation were applied to denervated muscles, either 5 Hz frequency (slow rhythm) in trains of 2 s repeated every 7 s or 40 Hz frequency (fast rhythm) in trains of 250 ms every 7 s. Both patterns of stimulation gave the same number of impulses per day (about 61 000). The lack of reinnervation in muscle was verified in a preliminary series of experiments by examination of muscle sections stained using a silver technique [36] to visualize the nerve, and by stimulation of the remaining nerve trunk; no muscular responses were elicited [19].…”
Section: Animalsmentioning
confidence: 95%